Microcredit Coverage in Malaysian Macroeconomic Context: An Evidence Using Panel Data Analysis - Selvaraj, Thilagarani; Abdul Karim, Zulkefly; Abdul Rahman, Aisyah; Chamhuri, Norshamliza (UUM Press, 2019)
This paper aims to examine the effect of macroeconomic condition on microcredit coverage in Malaysia. The Microcredit Organizations (MO) was established to complement the mainstream financial institutions, but challenges remain with microcredit performances associated with microcredit coverage. The paper accordingly investigates the effects of macroeconomic condition on microcredit coverage in the Malaysian context. To achieve the objective, the static panel data technique is adopted, which comprises 13 states and three Federal Territories in the country, spanning 2011 to 2015. The findings reveal the resiliency of MO towards macroeconomic conditions in Malaysia. The increase in the inflation rate and agriculture GDP (LNAGDP) share shows significant negative and positive effects (non-resilient) on microcredit coverage. The main findings will assist in addressing the newly identified macroeconomic condition to improve on micro credit performance. Policy implications emanating from the study are expected to be relevant to the government, MOs and borrowers. The government accordingly can make important contributions to borrowers by maintaining macroeconomic stability (inflation and LNAGDP share) through appropriate policies in order to achieve good microcredit coverage. MOs may revisit the existing quality regulation (MOs risk weighing loan disbursement) based on the macroeconomic condition which, in turn, can be used in outreaching more microcredit borrowers. Finally, this study may also help to elucidate specific understanding of the government and MO objectives in outreaching microcredit borrowers.